The Development of Animated Video Learning Media based Sparkol Videoscribe for Understanding Students’ Concept - Veby Penyustia; Eko Risdianto; Ahmad Syarkowi (Institut Agama Islam Negeri (IAIN) Curup, 2023)
The purpose of this study was to determine the feasibility of animated videos as well as to study reading of literature for the senior high school students in Bengkulu City. The method of this study was research and development (R&D) using the ADDIE model. The results of this study implied that the material feasibility test showed 88.75% material competency aspects, 77.85% concept understanding aspects, 85.71% material suitability aspects, 91.25% language aspects with an average of 84.77% which indicated perfectly feasible. Media feasibility test revealed 82.5% appropriateness aspects, 86% display aspect, 87.5% usage aspect, 73.33% advantage aspect, with an average acquisition of 82.5% which indicated highly excellence, small-scale readability test obtained 79.05% that was very good category. It can be concluded that the development of animated video learning media based sparkol videoscribe for understanding students’ concept was worthy to be tested. The animated videos are expected to attract users in both classroom and off-classroom self-study.